Conditional RAG-1 Mutants Block the Hairpin Formation Step of V(D)J Recombination - Kale, Sam B. (American Society for Microbiology, 2001)
Hairpin formation serves an important regulatory role in V(D)J recombination because it requires synapsis of an appropriate pair of recombination sites. How hairpin formation is regulated and which regions of the RAG proteins perform this step remain unknown. We analyzed two conditional RAG-1 mutants that affect residues quite close in the primary sequence to an active site amino acid (D600), and we found that they exhibit severely impaired recombination in the presence of certain cleavage site sequences. These mutants are specifically defective for the formation of hairpins, providing the first identification of a region of the V(D)J recombinase necessary for this reaction. Substrates containing mismatched bases at the cleavage site rescued hairpin formation by both mutants, which suggests that the mutations affect the generation of a distorted or unwound DNA intermediate that has been implicated in hairpin formation. Our results also indicate that this region of RAG-1 may be important for coupling hairpin formation to synapsis.